Foreign Minister meets UMP campus community - UMP, PNC (2018)
Foreign Minister Dato’ Saifuddin Abdullah attended a gathering with some 1,000 people at University Malaysia Pahang (UMP) that was held at Astaka Hall, UMP Gambang Campus on October 22, 2018.